IDS Medical System (idsMED) / Muhammad Zulfikar Abdullah - Abdullah, Muhammad Zulfikar (Faculty of Business and Management, 2025)
This report outlines my six-month internship at IDS Medical Systems (M) Sdn Bhd, where I was placed in the HR Department. My primary responsibilities revolved around recruitment and administrative functions, which involved sourcing candidates, conducting screening calls, arranging interviews, and managing employee records. I also participated in employee engagement activities, such as the Mini Olympic and Merdeka celebrations, where I contributed to organizing events and fostering a positive work environment. These experiences greatly enhanced my organizational, communication, and coordination skills, offering me practical insights into the HR processes. During my internship, I had the opportunity to work on the Project Falcon, where I updated employee provides in SAP SuccessFactors, which strengthened my understanding of HR data management and compliance. My exposure to modern HR tools, including Microsoft Outlook, Teams, and Spark hire, further improved my technical skills and knowledge of current recruitment practices. These experiences helped me grasp the significance of efficient HR data systems in enhancing organizational operations and employee management. Overall, my internship at IDS Medical Systems was a highly valuable learning experience. I gained a solid foundation in recruitment, HR data management, and event planning while developing essential skills such as communication, organization, and decision making. This internship has significantly contributed to my career development, providing me with the knowledge and skills necessary to succeed in human resource management or any field requiring strong interpersonal and organizational abilities. The mentorship and support I received from my colleagues and supervisor were essential to my growth, and I look forward to applying what I have learned in my future career.